1238Estimating the non-specific effects of seasonal influenza vaccine on RSV-hospitalisations in children. (2nd September 2021) - Le, Huong; Blyth, Christopher; Gidding, Heather; Snelling, Tom; Fathima, Parveen; Moore, Hannah
Abstract: Background: Seasonal influenza vaccine is effective against influenza hospitalisations, but little is known about non-specific effects on other respiratory pathogens with similar seasonal patterns. We aimed to assess the causal impact of seasonal influenza vaccine on laboratory-confirmed hospitalisations for respiratory syncytial virus (RSV) in children using an instrumental variable (IV) strategy. Methods: We used population-based probabilistically linked data on births, childhood immunisations, deaths, hospitalisations, perinatal and statewide microbiology data (2000-2013) in Western Australia (WA). Our analysis cohort included children up to age 7 years. We exploited WA's unique preschool influenza vaccination policy commencing in 2008 and used this as an instrument for vaccination status. We estimated a system of two simultaneous probit equations: determinants of influenza vaccine uptake, and determinants of RSV-confirmed hospitalisation. Results: Influenza vaccine coverage was low prior to 2008 but increased to 33.7% in children aged 6-23 months in 2009. RSV-hospitalisations ranged from 3.5/1000 children (12-23 months) to 6.4/1000 (6-12 months). Receipt of seasonal influenza vaccine reduced RSV-hospitalisations in the population cohort of children aged <2 years by an average of 0.21% in the same year (p < 0.001). Conclusions: To our knowledge, this is the first analysis utilising an IV estimation strategy to assess the impact of influenza vaccine on RSV-hospitalisations. We estimated a small, but highly statistically significant impact that warrants further investigation using contemporary data. Key messages: RSV is a leading cause of childhood morbidity. The role of influenza vaccine offering cross protection to RSV could be further explored prior to RSV vaccines being commercially available.